2017
DOI: 10.5114/wiitm.2017.69227
|View full text |Cite
|
Sign up to set email alerts
|

Two cases of laparoscopic total colectomy with natural orifice specimen extraction and review of the literature.

Abstract: We present two cases of natural orifice specimen extraction (NOSE) after laparoscopic total colectomy and ileorectal anastomosis (TC-IRA), and we also review all of the previously reported cases. Our aim was to focus on patient selection for NOSE after TC-IRA. The PubMed and Google Scholar databases were scanned. Demographic features, surgical indications, and techniques were analyzed. Basic calculations were used for statistical analysis. A total of 13 cases were detected in addition to our 2 cases. All of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…In our study, wound infections were not detected in the NOSE group, whereas in the transabdominal group, three patients (8.5%) developed infections at the specimen extraction area despite the routine, rigorous care with wound protector. When the literature was reviewed, this complication is as high as 20% in patients who undergo laparoscopic right hemicolectomy and transabdominal extraction 11 . In a previous study comparing the two techniques, no wound infections were seen in the NOSE group but two patients (5.8%) in the transabdominal group 6 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, wound infections were not detected in the NOSE group, whereas in the transabdominal group, three patients (8.5%) developed infections at the specimen extraction area despite the routine, rigorous care with wound protector. When the literature was reviewed, this complication is as high as 20% in patients who undergo laparoscopic right hemicolectomy and transabdominal extraction 11 . In a previous study comparing the two techniques, no wound infections were seen in the NOSE group but two patients (5.8%) in the transabdominal group 6 .…”
Section: Discussionmentioning
confidence: 99%
“…In our study, one patient in the transabdominal extraction group had a midline incisional hernia. In the literature, it is reported that the incidence of midline incisional hernia is as high as 8.7% in patients undergoing laparoscopic right hemicolectomy following transabdominal extraction 11 . In our study, no hernia was found in the suprapubic incision or in the NOSE group.…”
Section: Discussionmentioning
confidence: 99%
“…Natural orifice surgery is a technique developed to reduce the length of abdominal wall incision and to minimize the related complications. Transanal route as a field of extraction is used for benign tumors and occasionally for small volume malign tumors, but transvaginal tract is frequently used for larger lesions 1 . Isolated laparoscopic liver resection combined with transvaginal extraction has been reported before 2 ; however, transanal removal of a liver specimen has not been reported in the literature yet.…”
Section: Introductionmentioning
confidence: 99%